The right to dark night skies from administrative law - Rendón Huerta Barrera, Teresita (Universidad Nacional del Litoral, 2019)
The right to dark night skies from a legal location implies the opening of new horizons for administrative law, while the preservation of the sky free of light pollution, compromises the action of public entities in the regulation of multiple factors that go directly to the modification of the physical reality of the world around us and of life itself. While night lighting is an indispensable service for the operation of large cities, very little is known about the consequences of inefficient, unnecessary and extreme use of artificial light sources. The right to night skies without light pollution, implies adopting it within the framework of the values ​​of a society that continues in the loss of the natural and that as it advances in technology, has less free time. In general, for urbanized areas, a series of measures for the reduction of light pollution should be issued by local governments, from adequate public lighting, to the reduction of the level of lighting in shops and offices, as well as the Compliance with rules for the installation and operation of public and ornamental lighting.